Inductive noise coupling in multilayer superconductive ICs. (August 2022) - Krylov, Gleb; Friedman, Eby G.
Abstract: Superconductive cryogenic circuits are an emerging energy efficient technology that can replace or supplement existing CMOS VLSI systems. State-of-the-art superconductive circuits utilize more than ten niobium layers for the logic circuits and interconnect. Multiple sources of inductive coupling noise exist within these systems. In this paper, these inductive noise sources are evaluated and the effects of coupling noise are discussed. In particular, the effects of coupling noise within passive transmission lines, where the magnitude of the data signals is unusually small, are characterized and discussed. The effects of the bias current coupling to the inductors within the logic gates are also described, as the gates require accurate bias conditions. Guidelines to manage the deleterious effects of coupling noise are provided.